(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the role and importance of educational-didactic games in developing the creative abilities of preschool children. Based on modern pedagogical approaches, it analyzes how these games influence imagination, thinking, communication skills, and problem-solving abilities. The psychological impact of the play environment is also discussed as a factor that fosters creativity in early childhood.